Some aspects of political modernization in modern Uzbekistan - Izteleuova, Е.А. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2022)
The article analyzes the work of Sh. Mirziyoyev during his tenure as president. The author also tries to analyze the foreign and domestic policy of the Republic of Uzbekistan whenthe new President of the countrywas coming. In a short period of time, Sh.Mirziyoyevcarried out a colossal work. Anew stage of development a new stage of political, economic,and social reformsbeganfor Uzbekistan. The head of state managed to bring foreign policy to a completely different level. Within the framework of the Strategy of action on five priority directions of development of the Republic of Uzbekistan for 2017-2021, the new President outlined the main priority of Uzbekistan's foreign policy -Central Asia. Sh. Mirziyoyev voiced his intentions to create a belt of good neighborlinessand mutually beneficial cooperation in the Central Asian region. But implementing a multi-vector and balanced foreign policy, he managed to establish cooperation not only with neighboring republics but also with the leaders of world powers. The leader of the Republic of Uzbekistan shows his openness, readiness for dialogue, and strengthening of mutual trust and cooperation with all countries.